Macroprudential policy: A review - Ebrahimi Kahou, Mahdi; Lehar, Alfred (Journal of Financial Stability, 2017)
The severity and longevity of the recession caused by the 2007 financial crisis has highlighted the lack of a reliable macro-based financial regulation framework. As a consequence, addressing the link between the stability of the financial system as a whole and the performance of the overall economy has become a mandate for policymakers and scholars. Many countries have adopted macroprudential tools as policy responses for safeguarding the financial system. This paper provides a literature review of macroprudential policies, its objectives and the challenges that a macro-based framework needs to overcome, such as financial stability, procyclicality, and systemic risk.